Proceedings of the 11th International Conference on Human-Computer Interaction With Mobile Devices and Services 2009
DOI: 10.1145/1613858.1613866
|View full text |Cite
|
Sign up to set email alerts
|

Head tilting for interaction in mobile contexts

Abstract: Developing interfaces for mobile situations requires that devices are useable on the move. Here, we explore head tilting as an input technique to allow a user to interact with a mobile device 'hands free'. A Fitts' Law style evaluation is described where a user acquires targets, moving the cursor by head tilt. We explored position and velocity control cursor mechanisms in both static and mobile situations to see which provided the best level of performance. Results show that participants could successfully acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Within past PBLT research, nearly all studies have used the same control/interaction method, known as Positional control. However, results from pressure-based shape translation [13] and targeting through head tilt [4] have suggested that a velocity or Rate-based control may allow for better control of pressure or linear targeting (respectively), especially when the user is mobile. Therefore, in this paper we present two parts of one study looking at pressure input on mobile devices: one looking at how walking affects our ability to control pressure-based input and which control method allows for better control; and a second testing whether the same mobile interaction can be carried out with only audio feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Within past PBLT research, nearly all studies have used the same control/interaction method, known as Positional control. However, results from pressure-based shape translation [13] and targeting through head tilt [4] have suggested that a velocity or Rate-based control may allow for better control of pressure or linear targeting (respectively), especially when the user is mobile. Therefore, in this paper we present two parts of one study looking at pressure input on mobile devices: one looking at how walking affects our ability to control pressure-based input and which control method allows for better control; and a second testing whether the same mobile interaction can be carried out with only audio feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the wrist rotation study, users interacted both while static and mobile. Detailed statistical results can be found here [4]. There were significant differences found in the accuracy data between the static and mobile conditions using both position and velocity control.…”
Section: Head Tiltmentioning
confidence: 87%
“…Crossan et al [2] found that head tilt using rate-based control produced better accuracy than positional, at the cost of slower selection time, when users were walking. Conversely, they found that positional control allowed for superior accuracy and selection time when users were sitting.…”
Section: Control Methods and Mobilitymentioning
confidence: 99%
“…This study found that walking negatively affected accuracy when selecting 2 levels of pressure. Other work looking at how walking influences mobile interaction has also found negative effects on control accuracy when tapping on-screen with a finger [3] and during linear targeting via head tilt [2]. We therefore wanted to investigate 1) how mobility influences our ability to control pressure; 2) which control method, positional or rate-based, allows for more stable and accurate control of pressure when mobile; and 3) whether this knowledge can be used to design non-visual mobile pressure interaction as it has been shown that users can accurately apply pressure using only audio feedback while sitting [7].…”
Section: Control Methods and Mobilitymentioning
confidence: 99%
See 1 more Smart Citation